One-way road? Components of PCC expansion to Minas Gerais - Duarte, Thais Lemos; Araújo, Isabela Cristina Alves de (Tempo Social, 2020)
Based on analytical resources that address the belligerent, corporate and fraternal components proposed by the literature about the Primeiro Comando da Capital (PCC) criminal organization, this article examines different accounts about the group’s expansion in the state of Minas Gerais. The text analyses perspectives of state civil employees and prisoners at the Nelson Hungria Penitentiary (located in the greater metropolitan region of Belo Horizonte) that would have had some kind of connection to PCC. It shows that the civil actors highlighted, in particular, the belligerent and corporate aspects of the organization not only to characterize the criminal group, but also to justify the actions used to contain it. In turn, whilst the prisoners emphasized the fraternal aspects of the organization, they also did not disregard the importance of its warlike and corporate qualities in the process of expansion through the territory of Minas Gerais.